Global Research Alliance N2O chamber methodology guidelines: Recommendations for air sample collection, storage, and analysis. Issue 5 (26th August 2020) - Harvey, M. J.; Sperlich, P.; Clough, T. J.; Kelliher, F. M.; McGeough, K. L.; Martin, R. J.; Moss, R.
Abstract: Certain aspects in the collection, handling, storage, and subsequent analysis of discrete air samples from non‐steady‐state flux chambers are critical to generating accurate and unbiased estimates of nitrous oxide (N2 O) fluxes. The focus of this paper is on air sample collection and storage in small vials (<12 ml) primarily for gas chromatography (GC) analysis. Sample integrity is assured through following simple procedures including storage under pressure and analysis within a few months of collection. Concurrent storage of standards in an identical manner to samples is recommended and allows the storage period to be reliably extended. In the laboratory, an autosampler is typically used in batch analysis of ∼200 sequentially analyzed samples by GC with an electron capture detector (ECD). Some comparisons are given between GC and alternatives including optical N2 O detectors that are increasingly being used for high‐precision N2 O measurement. The importance of calibration and traceability of gas standards is discussed, where high‐quality standards ensure the most accurate assessment of N2 O concentration and comparability between laboratories. The calibration allows a consistent and best estimate of flux to be derived.